Prevalence of patients with acute kidney injury presenting to Tribhuvan University Teaching Hospital - Shrestha, Tirtha Man; Shakya, Yagya Laxmi; Neupane, Ram Prasad; Raut, Shankar; Ghimire, Rajan (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: Acute kidney injury is one of the most important causes of morbidity and mortality in hospitalized patients. AKI’s causes vary based on geographical regions, lifestyles, disease patterns, and management strategies. Thus, there might be differences in its prevalence in different parts of the world. Therefore, the study aims to evaluate the prevalence and demographic distribution, underlying causes, intervention, and outcome of acute kidney injury patients presented in emergency rooms.Method: This observational retrospective cross-sectional study was performed on patients with AKI who presented to the emergency room of Tribhuvan University of Teaching Hospital from 1 Sep 2019 to 31 Jan 2020. A structured data collection sheet was used to gather demographic, laboratory parameters, management, and outcome data.Result: A total of 253 AKI patients were enrolled in the study. The mean±SD age was 59.28±19.34 years. 147 (58.1%) were Male, and 106(41.9%) were female. The most common type of AKI was renal 183(72.33%) followed by prerenal 38(15.02%), and post-renal 32(12.65%). The most common etiologic cause of renal failure was UTI 73(28.9%), followed by pneumonia 56(22.1%). Mean urea, creatinine, sodium, and potassium levels were 12.03 mmol/L, 184.15 µmol/L, 135 mEq/L and 4.17 mEq/L, respectively. Only four patients needed dialysis, and two patients expired during hospital stay.Conclusion: The most typical cause of acute renal failure is renal causes, followed by pre-renal and post-renal. Infection remains the most preventable cause of AKI.